Controlled release study for captopril by using polymer carboxymethyl cellulose - Reem Ibrahim Mahdi; R.R. AL-Samarrai; Ahmed A.Ahmed (Tikrit Journal of Pure Science)
The present study was done to prepare tablet for captopril (CAP) which used in the treatment of hypertension and heart failure. CAP is mainly absorbed from the proximal intestine and to a lesser extent from the stomach. The tablets of CAP were prepared by using the polymer carboxymethyl cellulose (CMC) a captopril drug release system. The buffer solutions were use at (pH=12,7.4,8.5) as a media to release the drug similitude of the acidity index in stomach, in testiness, and blood plasma respective. It was accounted the concentrations of the drug that release in the above–mentioned solutions at the different temperature (25,30,37,40,45,) C°. The study was extended to the effect of the temperature and the acidity function on releasing the drug. The drug release from the polymers increased with  the temperature and the degree of the solution acidity. It was also studied the value of stability constant that increased with the temperature.